The lump of coal - Snicket, Lemony (HarperCollinsPublishers, 2008)
A lump of coal that wants to be an artist, but would settle for making decorative marks on a piece of grilled meat, rolls out of a forgotten bag of charcoal one winter and takes a spin through town seeking a miracle.